Collection of genetic data at scale for a nationally representative population: the UK Millennium Cohort Study. (January 2022) - Fitzsimons, Emla; Moulton, Vanessa; Hughes, David A; Neaves, Sam; Ho, Karen; Hemani, Gibran; Timpson, Nicholas; Calderwood, Lisa; Gilbert, Emily; Ring, Susan
Abstract : A DNA bank has been created from the Millennium Cohort Study (MCS) saliva samples. A total of 23, 336 samples are available, from 9, 259 cohort members (4, 630 males and 4, 629 females), 8, 898 mothers and 5, 179 fathers. There are 4, 533 mother, child, father 'triads'. This paper describes the collection of the saliva samples from cohort members and their biological parents in the MCS. It analyses response rates and predictors of response, and details the DNA extraction, genotyping and imputation procedures performed on the data.